Retinal astrocytic hamartoma and tuberous sclerosis: Case report - Case report - Ayd?n, Mustafa; Kurt, Nepe Ç?tak; Kabakup, Nimet; Y?ld?r?m, Hanefi (Kare Publishing, 2006)
Astrocytic tumors occur in retina usually as a part of phacomatosis and their isolated occurrence is rare. A eleven year-old case with bilateral multifocal retinal astrocytoma associated with tuberous sclerosis is presented in order to discuss the differential diagnosis of astrocytic hamartomas from intraocular malignencies, retinal or optic other lesions. Copyright 2001 - 2009 Hosting & Programlama Hipermedya.
Retinal astrositik hamartom ve tüberoz sklerozis: Olgu sunumu - Olgu sunumu
Keywords: Child; Retinal astrocytic hamartoma; Tuberous sclerosis